2008
DOI: 10.1161/strokeaha.107.505354
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic Diagnosis of Ischemic Stroke Subtypes With Plasma Biomarkers

Abstract: Background and Purpose-Because there is no biologic marker offering precise information about stroke etiology, many patients receive a diagnosis of undetermined stroke even after all available diagnostic tests are done, precluding correct treatment. Methods-To examine the diagnostic value of a panel of biochemical markers to differentiate stroke etiologies, consecutive acute stroke patients were prospectively evaluated. Brain computed tomography, ultrasonography, cardiac evaluations, and other tests were done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
219
3
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(242 citation statements)
references
References 34 publications
14
219
3
6
Order By: Relevance
“…A number of biomarkers have been found to distinguish cardioembolic from non-cardioembolic ischemic stroke. In 707 ischemic stroke patients, cardioembolic stroke was predicted by levels of BNP >76 pg/ml with 72% sensitivity and 69% specificity [35]. In the same study, D-dimer >0.96 g/mL predicted cardioembolic etiology with a 56% sensitivity and 64% specificity.…”
Section: Biomarkers Of Ischemic Stroke Etiologymentioning
confidence: 77%
“…A number of biomarkers have been found to distinguish cardioembolic from non-cardioembolic ischemic stroke. In 707 ischemic stroke patients, cardioembolic stroke was predicted by levels of BNP >76 pg/ml with 72% sensitivity and 69% specificity [35]. In the same study, D-dimer >0.96 g/mL predicted cardioembolic etiology with a 56% sensitivity and 64% specificity.…”
Section: Biomarkers Of Ischemic Stroke Etiologymentioning
confidence: 77%
“…While several markers, such as NT-BNP, 5,20,21 CRP, [21][22][23][24] D-Dimers, 20,25,26 Interleukin-6, 21,24,27 von Willebrand factor, 28, 29 S-100β, 30 and neuron specific enolase (NSE), 31 have been associated with functional outcome or mortality, only a few biomarkers added to prognosis based on clinical assessment. None of these markers, however, were fully evaluated including assessment of accuracy (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that low levels of sRAGE may be not only predictive of not only of stroke risk, 31,32 but also associated with subclinical cerebrovascular disease, particularly in ethnic groups with increased risk for cerebrovascular disease. 33 In the recent analysis of the CARDS study, 20 the hazard ratio for sRAGE and stroke was 0.66, but it did not reach levels of significance owing to the relatively low number (n ¼ 44) of stroke events.…”
Section: Discussionmentioning
confidence: 99%